Relationship of Knowledge, Attitudes And Behavior About Nutrition Balance with Nutritional Status of Student in Poltekkes Kemenkes Bengkulu in 2020 - thesa frovela (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
The health and nutritional status of pregnant women determined at teenager and adult during a eligible woman, so everyone must have knowledge, attitudes and behaviors about nutrition so that they don’t have mistakes in food selection. The purpose of this observation is determine the relationship between knowledge, attitudes, and behavior about nutritional balance with the nutritional status of students in Poltekkes Kemenkes Bengkulu in 2020. The design of this observation is obsevational cross-sectional design conducted in January in Poltekkes Kemenkes Bengkulu with a population of 640 people and a sample of 60 people. The statistical analysis used the pearson correlation test. The results showed that the average knowledge about balanced nutrition was good enough, the average attitude about balanced nutrition was good, the average behavior about balanced nutrition was good and the average nutritional status of female students was in the normal category. There is a relationship between knowledge about nutritional balance with nutritional status of student (r = 0.324), there is a relationship between attitudes about nutritional balance with nutritional status of student (r = 0.373), and there is a relationship between behavior about nutritional balance with nutritional status of student (r = 0.343). It is expected that students can improve their knowledge, attitudes and behaviors about nutritional balance.